2014
DOI: 10.13102/sociobiology.v59i2.618
|View full text |Cite
|
Sign up to set email alerts
|

Natural Biological Control of Diaphania spp. (Lepidoptera: Crambidae) by Social Wasps

Abstract: The social wasps (Hymenoptera: Vespidae) are important agents of biological control for agricultural pests. Diaphania hyalinata L. and Diaphania nitidalis Cramer (Lepidoptera: Crambidae) are among the main pests of plants in the Cucurbitaceae family. Although the importance of social wasps is acknowledged, little is known about their activity as biological control agents in Diaphania spp. Thus, this work aimed to study the natural biological control of the caterpillars D. hyalinata and D. nitidalis by social w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…The potential in harnessing predatory wasps in biocontrol was recognized over a century ago when Polistes paper wasps were identified as important predatory enemies of cotton worm Alabama argillacea [19,20,27]. More recent work has shown that wasps are common in a range of agricultural environments [28][29][30][31][32][33] and that pest lepidopterans form a main or significant portion of wasp forage [21,24,[34][35][36][37][38][39]. One concern is that the overall impact of predatory wasps on crop pests may be limited, as many pests hide within the plant, potentially making them inaccessible to hunting wasps.…”
Section: Introductionmentioning
confidence: 99%
“…The potential in harnessing predatory wasps in biocontrol was recognized over a century ago when Polistes paper wasps were identified as important predatory enemies of cotton worm Alabama argillacea [19,20,27]. More recent work has shown that wasps are common in a range of agricultural environments [28][29][30][31][32][33] and that pest lepidopterans form a main or significant portion of wasp forage [21,24,[34][35][36][37][38][39]. One concern is that the overall impact of predatory wasps on crop pests may be limited, as many pests hide within the plant, potentially making them inaccessible to hunting wasps.…”
Section: Introductionmentioning
confidence: 99%
“…This leads us to the necessity of other studies for any inference about the performance of these species as pollinators of Serjania caracasana. Some investigations of the use of Vespidae species have already gained interest in biological control of agricultural pests (Marques et al 1993 andPicanço 2014). It is probable that this plant can be object of study in an integrated pest management program, as a possible supplier of food to the species of interest as a biological control agent of pests.…”
Section: Discussionmentioning
confidence: 99%
“…Predatory wasps are common in a range of agricultural environments, suggesting that such crops provide rewarding forage patches (Bommarco et al ., 2011; Rodriguez et al ., 2012; Souza et al ., 2013; Jacques et al ., 2015, 2018; Tomazella et al ., 2018). Moreover, observational studies report social predatory wasps as one of the main natural predators of lepidopteran pests in agricultural settings (Rabb & Lawson, 1957; Picanço et al ., 2006, 2010; Bommarco et al ., 2011; Picanço, 2012; Pereira et al ., 2018; Lourido et al ., 2019) and that they can successfully locate such prey using olfactory cues (Pietrantuono, Moreyra & Lozada, 2018; Southon et al ., 2019). A third reason why social wasps are promising biocontrol agents is due to the sheer numbers of hunters provided by each colony; a single V. vulgaris colony has up to 10000 workers and produces thousands of larvae; Vespula has been suggested as a viable candidate for development as a manageable pest controller (Donovan, 2003).…”
Section: Regulating Servicesmentioning
confidence: 99%
“…Prezoto & Braga (2013) observed Synoeca cyanea predating the fig fly Zaprinus indianus , a pest to many fruit crops in Brazil; seven species of polistine wasps were observed naturally predating on the key tomato crop pest Tuta absoluta in Brazil (Picanço et al ., 2011). Observational studies like these clearly show that Vespidae wasps preferentially predate the larger 2nd–5th instar larvae (Gonring et al ., 2003; Picanço et al ., 2010; Picanço, 2012), without quantifying the impact of this on the prey population. These studies are only illustrative of foraging behaviour, not the foraging capacity of the wasp species, and so do not help estimate of the value of wasps as biological control agents.…”
Section: Regulating Servicesmentioning
confidence: 99%